Synthesis and Characterization of Nonsymmetric Liquid Crystal Dimer Containing Biphenyl and Azobenzene Moiety - S. Sandy Subala; B. Syama Sundar; S. Sreehari Sastry (Journal of Chemistry)
Calamitic liquid crystalline dimer containing azobenzene moiety and a decyloxy biphenyl linked by flexible spacers {4-[7-(4′-decyloxy-biphenyl-4-yloxy)-alkyloxy]-phenyl}-(4-decyl-phenyl)-diazene has been synthesized and characterized by spectroscopic methods. The transition temperatures and phase behaviours were studied by Differential Scanning Calorimeter (DSC) and Polarizing Optical Microscope (POM). The synthesized compounds exhibited enantiotropic liquid crystal phase with higher spacer display nematic and smectic C phases while lower spacer shows nematic and smectic A phases.